2010
DOI: 10.1017/s0022215110000757
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients with untreated age-related hearing loss

Abstract: The Short Form 36 Health Survey, a generic measure, lacked specificity and sensitivity in detecting clinically significant hearing loss. However, significant hearing impairment was reflected in the Hearing Handicap Inventory for the Elderly Screening Version questionnaire scores, suggesting that this is a good, disease-specific screening tool. A combination of functional (i.e. the Hearing Handicap Inventory for the Elderly Screening Version questionnaire) and physiological (i.e. audiometric) assessment is reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 32 publications
3
35
0
1
Order By: Relevance
“…This is in accordance with previous studies, e.g. Chew and Yeak (2010), and is consequently one important rationale for using questionnaires in the care of individuals with hearing impairment and furthermore in a research context. A systematic literature review concerning questionnaires demonstrated that Ͼ 50 different questionnaires have been used in different studies, and that the questionnaire most frequently used was published in six different studies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is in accordance with previous studies, e.g. Chew and Yeak (2010), and is consequently one important rationale for using questionnaires in the care of individuals with hearing impairment and furthermore in a research context. A systematic literature review concerning questionnaires demonstrated that Ͼ 50 different questionnaires have been used in different studies, and that the questionnaire most frequently used was published in six different studies.…”
Section: Discussionsupporting
confidence: 91%
“…For example, the Blue Mountain Hearing Study (2007) showed an association between bilateral hearing impairment and poorer SF-36 scores in both physical and mental domains and it also showed that poorer scores were associated with poorer hearing and that hearing-aid use in a 10-year follow-up was associated with higher scores (Chia et al, 2007;Dalton et al, 2003;Gopinath et al, 2012). Other studies have not demonstrated any impact on health-related quality of life in hearing-impaired individuals and it has been argued that generic instruments generally appear to be insensitive to the impact of a hearing loss (Parving et al, 2001;Chew & Yeak, 2010). Since the generic instruments are insensitive to the effect of hearing loss, the ability to show signifi cant changes in HRQL has been dependent on large sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Further background data is summarised in Table 1. Worthy of note, the hearing loss demonstrated by both groups was comfortably within the range considered to be clinically normal (<40 dB(HL) loss) (Chew & Yeak, 2010). Corresponding assessments are described below.…”
Section: Participantsmentioning
confidence: 76%
“…Doch sowohl im klinischen Alltag als auch aus der Literatur ist bekannt, dass die Ergebnisse der Tonschwellenaudiometrie nur bedingt mit den Ergebnissen der Sprachaudiometrie ohne und mit Hörge-räten korrelieren und die Resultate dieser beiden Methoden nur wenig mit dem Leiden und Handicap der Patienten über-einstimmen [11,12]. Wenn also die Korrelation von Handicap und Alltagsproblemen unabhängig vom Hörverlust und Sprachverstehen ist, muss dies separat erfasst werden, um das Ausmaß einer Hör-störung und die Veränderung nach Versorgung mit Hörhilfen treffend zu charakterisieren.…”
Section: Notwendigkeit Von Frageninventaren In Der Audiologischen Diaunclassified